Ko mất tính tổng quát, giả sử x2≥x1Ta có : x4x3=x3x2=x2x1≥1⇒x4≥x3≥x2≥x1Phương trình x2−3x+m=0 có 2 nghiệm x2≥x1làx2=3+√Δ12;x2=3−√Δ12 với Δ1=9−4m≥0 hay m≤94Phương trình x2−12x+n có 2 nghiệm x4≥x3làx4=6+√Δ2;x3=6−√Δ2 với đk Δ2=36−n≥0 hay n≤36∗x2x1=x4x3⇒3+√Δ13−√Δ1=6+√Δ26−√Δ2Nhân chéo rút gọn đc 2√Δ1=√Δ2(1) ∗x2x1=x3x2⇒x22=x1x3⇒(3+√Δ12)2=(3−√Δ12)(6−√Δ2)(2)Thế (1) vào (2), ta có (3+√Δ12)2=(3−√Δ12)(6−2√Δ1)⇒(3+√Δ12)2=(3−√Δ1)2⇒3+√Δ1=2(3−√Δ1)⇒√Δ1=1⇒Δ1=1⇒√Δ2=2⇒Δ2=4Ta có $\begin{cases} \Delta_1=1 \\ \Delta_2= 4\end{cases}\Rightarrow \begin{cases}9-4m=1= \\ 36-n=4 \end{cases}\Leftrightarrow \color{red}{\begin{cases}x=2 \\ y=32 \end{cases}} $ (thõa đk)
Ko mất tính tổng quát, giả sử
x2≥x1Ta có :
x4x3=x3x2=x2x1≥1⇒x4≥x3≥x2≥x1Phương trình
x2−3x+m=0 có
2 nghiệm
x2≥x1làx2=3+√Δ12;x2=3−√Δ12 với
Δ1=9−4m≥0 hay
m≤94Phương trình
x2−12x+n có
2 nghiệm
x4≥x3làx4=6+√Δ2;x3=6−√Δ2 với đk
Δ2=36−n≥0 hay
n≤36∗x2x1=x4x3⇒3+√Δ13−√Δ1=6+√Δ26−√Δ2Nhân chéo rút gọn đc
2√Δ1=√Δ2(1) ∗x2x1=x3x2⇒x22=x1x3⇒(3+√Δ12)2=(3−√Δ12)(6−√Δ2)(2)Thế
(1) vào
(2), ta có
(3+√Δ12)2=(3−√Δ12)(6−2√Δ1)⇒(3+√Δ12)2=(3−√Δ1)2⇒3+√Δ1=2(3−√Δ1)⇒√Δ1=1⇒Δ1=1⇒√Δ2=2⇒Δ2=4Ta có $\begin{cases} \Delta_1=1 \\ \Delta_2= 4\end{cases}\Rightarrow \begin{cases}9-4m=1= \\ 36-n=4 \end{cases}\Leftrightarrow \color{red}{\begin{cases}
m=2 \\
n=32 \end{cases}} $ (thõa đk)